Endovascular Recanalization for Chronic Symptomatic Intracranial Vertebral Artery Total Occlusion. (3rd September 2014) - Xu, Ziqi; Ma, Ning; Mo, Dapeng; Wong, Edward Ho chung; Gao, Feng; Jiao, Liqun; Miao, Zhongrong
Abstract : Purpose. The outcome of recanalization in patients with chronic symptomatic intracranial vertebral artery (ICVA) total occlusion is poor. This paper reports the technical feasibility and long-term outcome of ICVA stenting in patients with chronic symptomatic total occlusion. Methods. Retrospective review of our prospectively maintained intracranial intervention database to identify patients with symptomatic total occlusion of ICVA with revascularization attempted >1 month after index ischemic event. Results. Eight patients (mean age 58 years) were identified. One had stroke and 7 had recurrent transient ischemic attacks. Four had bilateral ICVA total occlusion and 4 had unilateral ICVA total occlusion with severe stenosis contralaterally. Seven of 8 patients underwent endovascular recanalization, which was achieved in 6. Periprocedural complications included cerebellum hemorrhage, arterial dissection, perforation, and subacute in-stent thrombosis which occurred in 3 patients. One patient died of cerebellum hemorrhage. The other patients improved clinically after endovascular therapy. Conclusions. Stent-supported recanalization of ICVA total occlusion is technically feasible, and may become a viable treatment option in selected patients.